Can Peripheral Arterial Tonometry and Biomarkers Help Identify Women Who Will Have Progressively Worsening Hypertensive Disorders of Pregnancy? - Clifford, Caitlin M.; Hesson, Ashley M.; Sangtani, Ajleeta; Ganesh, Santhi K.; Langen, Elizabeth S. (American Journal of Perinatology, 2024)
Objective This study aimed to (1) evaluate whether endothelial dysfunction, as measured by peripheral arterial tonometry (PAT) indices and biomarker (soluble fms-like tyrosine kinase-1 [sFLT], brain natriuretic peptide [BNP]) levels at 34 weeks gestation, can predict progression from nonsevere to severe hypertensive disorders of pregnancy (HDPs); and (2) develop a clinical risk model for prediction of progression from nonsevere to severe HDP.Study Design We prospectively enrolled patients with a singleton gestation carrying a nonsevere HDP diagnosis. Forty-five participants were enrolled for PAT evaluation and serum collection between 340/7 and 366/7 weeks. PAT indices (e.g., Augmentation Index normalized to a heart rate of 75 bpm [AI75]) and biomarker concentrations were assessed at enrollment. The primary outcome was progression from a nonsevere diagnosis in the late preterm period to a diagnosis of preeclampsia with severe features or superimposed preeclampsia. Statistical analyses included two-sample t-tests, Fisher's exact tests, and multivariate modeling.Results Thirteen subjects (30%) progressed to severe disease. No significant differences in mean PAT indices between the outcome groups were found. We found a significant difference in mean sFLT values between the two groups (p = 0.02, area under the curve [AUC] of 0.609), but not in mean BNP values. An endothelial dysfunction index (presence of fetal growth restriction, “high” AI75, and positive systolic blood pressure slope) discriminated between progression and nonprogression (p = 0.03, AUC of 0.707).Conclusion sFLT level was a marker of progression from nonsevere to severe HDP. Further, a novel endothelial dysfunction index discriminated between progression and nonprogression to severe disease with good performance.Key Points
Keywords: peripheral arterial tonometry; fms-like tyrosine kinase-1; brain natriuretic peptide; endothelial dysfunction; hypertensive disorders of pregnancy